160k views
2 votes
How do I solve for n in this equation:
-6n-20=-2n+4(1-3n)

User Vikas
by
4.5k points

1 Answer

4 votes

Answer:

-6n-20=-2n+4(1-3n)

Solution

The bracket should be expanded

-6n-20=-2n+4-12n

Then we collect the like terms

-6n + 2n+12n = 20+4

8n=24

Now divide both sides by 8

8n/8 =24/8

n = 3

You can now insert 3 into anywhere you see n and see how it goes

-6n-20= -2n + 4(1-3n)

-6(3) - 20 = -2(3) + 4[ 1-3(3)]

-18 -20= -6 + 4(1-9)

-38= -6 -32

-38= - 38

That's all

Explanation:

User Kongress
by
4.7k points